An Application of the Four Brahmaviharas to the Operational Performance of Personnel at Kho Hong Municipality, Hat Yai District, Songkhla Province - Sookkatorn, Phrapalad Ekkarin Sumedho; Kuasing, Somporn; Thanchom, PhraSarawin Surapanyo (Journal of Dhamma for Life, 2026)
The objectives of This thesis paper are as follows: 1) to study an application of the four Brahmaviharas to the operational performance of personnel at Kho Hong municipality, Hat Yai district, Songkhla province, Had Yai District Songkhla Province; and 2) to examine guidelines for promoting an application of the four Brahmaviharas to the operational performance of personnel at Kho Hong municipality, Hat Yai district, Songkhla province. This study is quantitative research. The population consisted of 181 personnel of Kho Hong Municipality, Hat Yai District, Songkhla Province. A sample of 123 respondents was selected using simple random sampling by lottery. The research instrument was a questionnaire. Data were analyzed using frequency, percentage, mean, standard deviation, and descriptive content analysis. The results of the research found that 1) An application of the four Brahmaviharas to the operational performance of personnel at Kho Hong municipality, Hat Yai district, Songkhla province, Had Yai District Songkhla Province was overall at a high level. When considered by aspect and ranked by mean scores from highest to lowest, the aspect with the highest mean was Mudita, which was at a high level, followed by Metta, also at a high level. The aspect with the lowest mean was Upekkka, which was likewise at a high level, respectively. 2) The guidelines for promoting an application of the four Brahmaviharas to the operational performance of personnel at Kho Hong municipality, Hat Yai district, Songkhla province, Hat Yai District Songkhla Province include prioritizing tasks and completing urgent work first; applying rational principles and relying primarily on factual evidence; cultivating a sense of mutual assistance in the workplace; consulting and discussing when problems arise; and organizing activities that promote unity within the organization. In addition, expressions of congratulations, praise, and encouragement should be given when work performance improves or achievements are attained. The organization should also establish clear and definite criteria for promotion, avoiding arbitrary decisions. Furthermore, fairness should be provided equally to all personnel, with impartiality maintained by not favoring one’s own group or wrongdoers, adhering strictly to rules and regulations, and imposing disciplinary actions on those who commit violations.